Defining the aetiology of erectile dysfunction in men with chronic pelvic pain syndrome. (21st February 2013) - Mehta, Akanksha; Stember, Doron S.; O'Brien, Keith; Mulhall, John P.
Summary Men presenting with chronic pelvic pain syndrome (CPPS) frequently report concomitant erectile dysfunction (ED), but the underlying cause of ED in this patient population has not been previously studied. This study prospectively investigated the aetiology of ED in men with CPPS. The study population comprised 46 men with penile pain or dysorgasmia, and concomitant ED. All participants completed the NIH‐CPSI and international index of erectile function‐ erectile function domain (IIEF‐EFD) questionnaires, and underwent penile duplex Doppler ultrasonography (DUS), following intracavernosal trimix injection, to evaluate erectile hemodynamic parameters. Pearson's correlation between NIH‐CPSI and IIEF‐EFD scores, and between NIH‐CPSI score and the erectile response to trimix injections was investigated. The prevalence of mild, moderate and severe CPPS symptoms was 26, 48 and 26% respectively. The severity of ED was mild, moderate or severe in 15, 61 and 24% of men respectively. NIH‐CPSI and IIEF‐EFD scores were negatively correlated (r = −0.32, p = 0.002). Peak systolic velocity (PSV) and end‐diastolic velocity (EDV) were normal in 96 and 100% of men respectively. The majority of men (78%) required ≥2 trimix injections to attain an adequate erection for DUS. NIH‐CPSI scores and the number of trimix injections needed were positively correlated (r = 0.22, p = 0.035). The aetiology of erectile dysfunction in men who present with CPPS and concomitant ED is almost always psychogenic. Penile DUS in this population of men is fraught with the potential for error, and frequently necessitates more than one dose of a vasoactive agent.